The play therapist's language of change releasing children's creative capabilities - Landreth, Garry; Play Therapy Institute (Texas : Play Therapy Institute, 2003)
Lecture on making contact with children through play therapy. Discusses characteristics of facilitative responses, process of helping children learn self responsibility, and suggests ways to keep the child in the lead in the therapeutive process. Also, demonstrates how to respond to issues and questions children present in play therapy
Title from title screen
DVD Format
Keywords: Play therapy; Play; Child psychology